Are Article Influence Scores Comparable across Scientific Fields? - Julie Arendt (Issues in Science and Technology Librarianship)
The Impact Factors provided in Journal Citation Reports (JCR) have been used as a tool for librarians, authors and administrators to assess the relative importance of journals. One limitation of the Impact Factor is that the values are not comparable across different fields of research. JCR now also includes Article Influence Scores. One of the reputed advantages of the Article Influence Score is that it takes into account differences in the citation patterns between fields, allowing for better comparisons across different fields. This study investigates the ability of the Article Influence Score to provide this advantage by comparing the Impact Factors and Article Influence Scores of 172 fields listed in the JCR Science Edition. Although the range of Article Influence Scores across different fields is less extreme than the range of Impact Factors, Article Influence Scores still display large differences across fields. The Article Influence Scores of scientific fields correlate with their Impact Factors. The scientific fields that have journals with higher Impact Factors also have journals with higher Article Influence Scores. For practical applications, the large disciplinary differences that persist in the Article Influence Score limit its utility for comparing journals across different fields. [ABSTRACT FROM AUTHOR]